The municipal territorial ordering: an approach from Colombia - Ramírez, Ricardo (2004)
Imaginary on the territorial ordering, technical, economic, social and administrative limitations; as well as the positive things are scrutinized in order to contribute elements for the debate on the plans of the territorial ordering. The political-administrative division is the one that presents the greatest difficulties, giving as a result differences that substantially modify the territories.